Model DKIW dalam Berbagi Pengetahuan - Pertiwi, Asri (LPPM of STIMIK ESQ, 2016)
Knowledge creation is one of the part of knowledge management that is enable for organizations to establish their competitive advantage. In the process of knowledge creation, there is the knowledge sharing activities. These activities will involve knowledge providers. They are the givers and the receivers. Some literatures focus on the givers only and forget about the receivers. This article discusses about how importance the role of knowledge receiver in the terms of knowledge creation. We use DIKW model in Knowledge Management for the discussion.